TWO DECADES OF REPRESSION: THE PERSISTENCE OF AUTHORITARIAN CONTROLS ON THE MASS MEDIA IN CENTRAL ASIA - FREEDMAN, Eric; SHAFER, Richard; ANTONOVA, Slavka (CENTRAL ASIA AND THE CAUCASUS, 2010)
Dissolution of the Soviet Union in 1991 gave birth to five independent nations in Central Asia—Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan—with initial aspirations for an imminent transition from communism toward democracy. After twenty years, however, none has developed anything close to a free press system or otherwise emerged from post-communist authoritarianism. To the contrary, each representation regime—meaning both authoritarian in governance and repressive in human rights practices—imposes extensive official and extra-official constraints on the mass media. Those constraints apply both to traditional outlets such as newspapers and broadcast stations and, increasingly, to new media such as news-related websites and blogs. After an overview of the Soviet press system, this article describes some of the abysmal restrictions confronting journalists and news organizations in contemporary Central Asia. It then suggests some factors that may explain the dearth of free press systems there, examines the impact of Western trainers and educators, and highlights limitations on the Internet’s ability to provide the public with alternative sources of news, information, and opinion. It ends with a pessimistic prognosis for development of sustainable free press systems. In the first years of independence, the five governments understandably regarded the press as a unifying tool to nurture national identity and a sense of statehood among their ethnically and linguistically diverse populations.1 That role for the press provided a relatively easy psychological transition for professional journalists. That is because they were educated, trained, and experienced in a system where the press served as a tightly controlled mouthpiece for the Communist Party, Marxist-Leninist philosophy, and the central government in distant Moscow.2 It was also a logical approach for the new national leaders, all of whom had headed their pre-independence Soviet republics. Yet such an advocacy-boosterism persona for the press deterred and discouraged many highly motivated journalists—especially new professionals and those who had chafed under the Soviet-era propagandizing mission—from pursuing fact-based, objective journalism based on a commitment to fairness, balance, ethics, and accuracy.